1D Ni–Co oxide and sulfide nanoarray/carbon aerogel hybrid nanostructures for asymmetric supercapacitors with high energy density and excellent cycling stability. Issue 36 (30th August 2016) - Hao, Pin; Tian, Jian; Sang, Yuanhua; Tuan, Chia-Chi; Cui, Guanwei; Shi, Xifeng; Wong, C. P.; Tang, Bo; Liu, Hong
Abstract : 1D Ni–Co oxide and sulfide nanoarray/carbon aerogel nanostructure based asymmetric supercapacitors display high energy density and excellent cycling stability. Abstract : The fabrication of supercapacitor electrodes with high energy density and excellent cycling stability is still a great challenge. A carbon aerogel, possessing a hierarchical porous structure, high specific surface area and electrical conductivity, is an ideal backbone to support transition metal oxides and bring hope to prepare electrodes with high energy density and excellent cycling stability. Therefore, NiCo2 S4 nanotube array/carbon aerogel and NiCo2 O4 nanoneedle array/carbon aerogel hybrid supercapacitor electrode materials were synthesized by assembling Ni–Co precursor needle arrays on the surface of the channel walls of hierarchical porous carbon aerogels derived from chitosan in this study. The 1D nanostructures grow on the channel surface of the carbon aerogel vertically and tightly, contributing to the enhanced electrochemical performance with ultrahigh energy density. The energy density of NiCo2 S4 nanotube array/carbon aerogel and NiCo2 O4 nanoneedle array/carbon aerogel hybrid asymmetric supercapacitors can reach up to 55.3 Wh kg −1 and 47.5 Wh kg −1 at a power density of 400 W kg −1, respectively. These asymmetric devices also displayed excellent cycling stability with a capacitance retention of about 96.6% and 92% over 5000 cycles.